Holographic projection based on programmable axilens. (December 2019) - Shen, Chuan; Hong, QingQing; Zhu, QinQin; Zu, Ci; Wei, Sui
Highlights: The holographic projection system based on programmable axilens extends the DOF. Different reconstruction distances can be achieved by changing the focal depth of the axilens. The reconstructed images in good focus can be simultaneously observed on a multi-plane in a range. Abstract: In a traditional holographic projection system, a clear reconstructed image is formed only in the focal plane of the Fourier lens. In this paper, We propose a novel method to form simultaneously holographic reconstructed images in good focus located at different planes. The large focal depth characteristic of the programmable axilens is applied to the holographic projection. First, the iterative Fourier algorithm is employed to generate a phase hologram. A new phase distribution is formed by superimposing the axilens phase on the phase hologram, and loading onto the phase-only liquid crystal on silicon (LCoS); With the programmability of the LCoS, the different focal-depth parameters of the axilens are tuned. We could obtain the desired holographic reconstructed images when the collimated laser is used to incident the LCoS. The experimental results show that compared with the holographic projection system based on Fresnel lens, the holographic reconstructed images in good focus can be observed simultaneously on a multi-plane in a range by dynamically changing the focal depth of the axilens.